2018
DOI: 10.3389/fmicb.2018.00425
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Selective Sweeps of Microcystis Population Detected by the Leader-End CRISPR Fragment Analysis in a Natural Pond

Abstract: The freshwater cyanobacterium Microcystis aeruginosa frequently forms toxic massive blooms and exists in an arms race with its infectious phages in aquatic natural environments, and as a result, has evolved extremely diverse and elaborate antiviral defense systems, including the clustered regularly interspaced short palindromic repeats (CRISPR)-CRISPR-associated genes (Cas) system. Here, to assess Microcystis population dynamics associated with exogenous mobile genetic elements such as phages and plasmids, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 43 publications
(86 reference statements)
0
20
0
Order By: Relevance
“…Generally, narrow-host-range viruses are thought to infect highly abundant hosts, whereas broad-host-range viruses are assumed to infect lowabundance hosts (17,47). According to our previous study (28), the Microcystis bloom at Hirosawanoike Pond comprises at least 16 major and other rare CRISPR genotypes, supporting the cooccurrence of narrow-and broad-host-range Microcystis viruses. Additionally, the transcriptional activities of the MVGFs did not necessarily reflect the abundances of each viral contig in the environment (Fig.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Generally, narrow-host-range viruses are thought to infect highly abundant hosts, whereas broad-host-range viruses are assumed to infect lowabundance hosts (17,47). According to our previous study (28), the Microcystis bloom at Hirosawanoike Pond comprises at least 16 major and other rare CRISPR genotypes, supporting the cooccurrence of narrow-and broad-host-range Microcystis viruses. Additionally, the transcriptional activities of the MVGFs did not necessarily reflect the abundances of each viral contig in the environment (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…Identification and characterization of novel Microcystis viruses. Eutrophication and Microcystis blooms occur at Hirosawanoike Pond from early summer to autumn every year due to the high nutrient input derived from agricultural activities (27)(28)(29). The phycocyanin intergenic spacer (PC-IGS) gene copy numbers of M. aeruginosa fluctuated from 4.2 Ï« 10 5 to 1.7 Ï« 10 6 copies/ml, showing that M. aeruginosa formed a dense bloom during sampling ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are diverse genotypes even within a single bacterial species in the environment, as observed in metagenomic islands, which are under-represented regions among all the genomes of one bacterial species (Rodriguez-Valera et al, 2009;Rodriguez-Valera and Ussery, 2012). For example, Microcystis blooms are composed of highly diverse genotypic populations (Yoshida et al, 2005;Kuno et al, 2014;Yang et al, 2015;Kimura et al, 2018). Thus, recent understanding of the virus-host coexistence relies on the concept of multiple genotype (strain)-level interactions at the species or population level (Thingstad et al, 2015), which encompass a range from highly resistant to susceptible host cells and from broad and narrow host range cyanoviruses (Morimoto et al, 2019).…”
Section: Competitive Evolution Between Cyanoviruses and Freshwater Blmentioning
confidence: 99%
“…The coexistence of diverse host genotypes within the population can be established by the viral infection of the dominant host genotype (Thingstad et al, 2014(Thingstad et al, , 2015. The ecological consequences of such viral control have been intensively studied in M. aeruginosa and indicated that multiple Microcystis populations possessing different CRISPR arrays exist in their massive blooms (Kuno et al, 2012(Kuno et al, , 2014 and oscillate in the environment (Kimura et al, 2018). Such continuous interactions have also been predicted between A. flos-aquae and its cyanovirus vB_AphaS-CL131 (Ć ulčius et al, 2019).…”
Section: Competitive Evolution Between Cyanoviruses and Freshwater Blmentioning
confidence: 99%